Cross-border commuting and consuming: an empirical investigation - Thomas Y. Mathä; Alessandro Porpiglia; Michael Ziegelmeyer (European Central Bank (ECB), 2014)
This paper analyses empirically how cross-border consumption varies across product and services categories and across household characteristics. It focuses on the part of cross-border sales that arise due to work-related cross-border crossings; it analyses the cross-border consumption behaviour of cross-border commuter households residing in Belgium, France and Germany and working in Luxembourg. In total, it is estimated that these households spend exteuro925 million per annum in Luxembourg, reflecting about 17% of their gross annual income from Luxembourg and contributing about 10% to total household final consumption expenditure in Luxembourg. Cross-border consumption expenditure is shown to depend on individual and household characteristics, such as total household income, the number of cross-border commuters in the household, distance between home and work, as well as price level (index) differences between Luxembourg and its neighbouring countries. Cross-border commuters take advantage of existing arbitrage opportunities.
Keywords: F15; R12; R23; J61; 330; commuting; Consumption; cross-border shopping; expenditure; households